Modulating Inhibitory Control Processes Using Individualized High Definition Theta Transcranial Alternating Current Stimulation (HD θ-tACS) of the Anterior Cingulate and Medial Prefrontal Cortex - Klírová, Monika; Voráčková, Veronika; Horáček, Jiří; Mohr, Pavel; Jonáš, Juraj; Dudysová, Daniela Urbaczka; Kostýlková, Lenka; Fayette, Dan; Krejčová, Lucie; Baumann, Silvie; Laskov, Olga; Novák, Tomáš (Frontiers in Systems Neuroscience, 2021)
Increased frontal midline theta activity generated by the anterior cingulate cortex (ACC) is induced by conflict processing in the medial frontal cortex (MFC). There is evidence that theta band transcranial alternating current stimulation (θ-tACS) modulates ACC function and alters inhibitory control performance during neuromodulation. Multi-electric (256 electrodes) high definition θ-tACS (HD θ-tACS) using computational modeling based on individual MRI allows precise neuromodulation targeting of the ACC via the medial prefrontal cortex (mPFC) and optimizes the required current density with a minimum impact on the rest of the brain. We therefore tested whether the individualized electrode montage of HD θ-tACS with the current flow targeted to the mPFC-ACC compared with a fixed montage (non-individualized) induces a higher post-modulatory effect on inhibitory control. Twenty healthy subjects were randomly assigned to a sequence of three HD θ-tACS conditions (individualized mPFC-ACC targeting; non-individualized MFC targeting; and a sham) in a double-blind cross-over study. Changes in the Visual Simon Task, Stop Signal Task, CPT III, and Stroop test were assessed before and after each session. Compared with non-individualized θ-tACS, the individualized HD θ-tACS significantly increased the number of interference words and the interference score in the Stroop test. The changes in the nonverbal cognitive tests did not induce a parallel effect. This is the first study to examine the influence of individualized HD θ-tACS targeted to the ACC on inhibitory control performance. The proposed algorithm represents a well-tolerated method that helps to improve the specificity of neuromodulation targeting of the ACC.